THE EFFECT OF PLAY-BASED LEARNING ON THE LEVEL OF MOTOR ABILITY OF STUDENTS AT STATE ELEMENTARY SCHOOL 020267 BINJAI - Hasni Aulia Rahmita; Nasution, Usman; Suprayitno; Ibrahim; Damanik, Saipul Ambri (Universitas Negeri Medan, 2025)
This study aims to determine the effect of play-based learning on the level of motor skills of students at State Elementary School 020267 Binjai. The background of this study is based on the importance of developing motor skills in elementary school-aged children through a fun learning approach, according to the child's physical development stage. Play-based learning is believed to provide varied motor stimulation and stimulate active physical activity, so that it can improve students' motor skills optimally. The method used in this study is pre-experimental with a one group pretest-posttest design. The subjects in this study were 20 fifth-grade students of State Elementary School 020267 Binjai. Data collection techniques were carried out by testing motor skills before (pretest) and after (posttest) the play-based learning treatment. The instrument used was a motor skills test that included aspects of coordination, balance, agility, and strength. The results of data analysis showed a significant increase in students' motor skills after being given play-based learning. This was indicated by the difference in pretest and posttest scores analyzed using a t-test, where the t-test value was obtained > t-table at a significance level of 0.05. Thus, it can be concluded that play-based learning has a positive effect on improving students' motor skills at SD Negeri 020267 Binjai.